Manajemen Risiko Usahatani Tembakau Kasturi Menghadapi Kondisi Perubahan Iklim (Studi Kasusu Kelompok Tani “ Surya Tani” Desa Sumberpinang Kecamatan Pakusari Kabupaten Jember) - Moh. Samsul Arifin; Ratih Apri Utami; Izza Orvala; Brian Nurmahadi (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
The purpose of this study was to determine the risk management applied by the farmer group